Complex facial reconstruction by vascularized composite allotransplantation: The first Belgian case. Issue 3 (March 2015) - Roche, Nathalie A.; Vermeersch, Hubert F.; Stillaert, Filip B.; Peters, Kevin T.; De Cubber, Jan; Van Lierde, Kristiane; Rogiers, Xavier; Colenbie, Luc; Peeters, Patrick C.; Lemmens, Gilbert M.D.; Blondeel, Phillip N.
Summary Introduction Complex injuries to the central part of the face are difficult to reconstruct with the current plastic surgery methods. The ultimate one-staged approach to restore anatomy and vital facial functions is to perform a vascularized composite allotransplantation (VCA). Methods A 54-year-old man suffered from a high-energy ballistic injury, resulting in a large central facial defect. A temporary reconstruction was performed with a free plicated anterolateral thigh (ALT) flap. Considering the goal to optimally restore facial function and aesthetics, VCA was considered as an option for facial reconstruction. A multidisciplinary team approach, digital planning, and cadaver sessions preceded the transplantation. Results A digitally planned facial VCA was performed involving the bilateral maxillae, the hard palate, a part of the left mandible, and the soft tissues of the lower two-thirds of the face. Due to meticulous preparations, minimal adjustments were necessary to achieve good fitting in the recipient. At week 17, a grade 4 rejection was successfully treated; sensory and motor recovery was noted to occur from the fourth postoperative month. Several serious infectious and medical problems have occurred until 15-months postoperatively; following that, the clinical situation has remained stable. Two years postoperatively, the patient and his family are very satisfied with the overall outcome and social reintegration in the community is successful. Conclusion The first face transplant in Belgium (#19 worldwide) was successful because of a meticulous 3-year preparation by a large multidisciplinary team. In our experience, preparatory cadaver dissections and three-dimensional (3D) computed tomographic (CT) modeling were valuable tools for an optimal intraoperative course and good alignment of the bony structures. Continuous long-term multidisciplinary follow-up is mandatory for surveillance of the complications associated with the immunosuppressive regime and for functional assessment of the graft.